Defining the Cervical Transformation Zone and Squamocolumnar Junction: Can We Reach a Common Colposcopic and Histologic Definition?. (November 2017) - Reich, Olaf; Regauer, Sigrid; McCluggage, W.G.; Bergeron, Christine; Redman, Charles
Abstract : Quality assurance and research in colposcopy and cervical pathology require standardized terminologies and reporting. However, clinical and histologic definitions of the cervical transformation zone (TZ) and squamocolumnar junction (SCJ) vary considerably. We aimed to identify areas of agreement and areas where work is required to standardize the definitions of the TZ and the SCJ. We conducted a survey among the board members of the European Federation of Colposcopy member societies and members of the International Society of Gynecological Pathologists. Overall, 22 expert colposcopists and 34 gynecologic pathologists responded. There was broad agreement that the TZ is the area where squamous metaplasia has occurred. There was consensus that the original SCJ can appear colposcopically indistinct in cases of maturation of the metaplastic squamous epithelium but can be identified histologically by the presence of the so-called last cervical gland. It was agreed that the border between the metaplastic squamous epithelium and the columnar epithelium on the surface of the cervix is called the new SCJ. Areas where work is required include the questions as to whether the cervical crypts lined by columnar epithelium in the field of squamous metaplasia are an integral part of the TZ or not and whether the individual microscopic borders between the metaplastic squamous epithelium of glandular crypts and the residual columnar epithelium of glandular crypts should be considered as part of the new SCJ or not. This paper is a step in an attempt to standardize colposcopic and histologic definitions among colposcopists and pathologists.